Enhancing Public Service Efficiency through Agile Governance: A Case Study in Surabaya - Kristina, Irene Yuma; Tamrin, M. Husni; Pancasilawan, Ramadhan (JPAP: Jurnal Penelitian Administrasi Publik, 2024)
This research aims to analyze the application of Agile Governance principles in the Pakis Subdistrict Office, Surabaya City in order to improve the quality of public services at the Surabaya City Population and Civil Registration Service. The proposition of this research is that implementing Agile Governance can increase efficiency and public satisfaction with public services. The research method used is a case study with a qualitative descriptive approach. The research results show that the application of Agile Governance principles, such as Good Enough Governance, Human Focused, Based on Quick Wins, and Simple Design and Continuous Refinement, has been quite effective in providing fast and efficient services to the community. However, the main findings reveal that the application of the Human Focused dimension is not optimal. The existing public complaint space does not always receive an adequate response, so it does not fully meet community expectations.